Economic Impact of Community Activities in Ruteng Nature Tourism Park Area, East Nusa Tenggara Province - Sari, Yovita Ratna; Sundawati, Leti; Sunkar, Arzyana (Media Konservasi, 2026)
This study addresses a gap in understanding the specific economic impacts of community engagement in Ruteng Nature Tourism Park (TWA Ruteng) on local livelihoods. While prior research highlights general benefits of tourism, limited attention has been given to the direct economic activities and their outcomes within TWA Ruteng. The objectives of this research are to analyze the economic activities of the Ngkiong Ndora Village community and evaluate their effects on household income. Data collection was conducted through interviews, observations, documentation, and literature review. Participants were categorized into three strata based on land ownership: 34 respondents in stratum I, 60 in stratum II, and 12 in stratum III. The data were analyzed using both quantitative and qualitative methods to provide a comprehensive understanding of economic dynamics. The results reveal that the community engages in land cultivation, wood utilization, and the exploitation of non-timber resources. These activities have a significant positive economic impact, contributing 76.44% to household income and increasing income levels by 76.94%. This study offers novel insights into the interaction between local communities and nature tourism parks, particularly in Indonesia. It highlights the importance of integrating community involvement into tourism development strategies and illustrates how such engagement can yield substantial economic benefits. Additionally, it provides empirical evidence to inform policies that balance conservation efforts with local economic development, ensuring sustainability and improved livelihoods.